Thermodynamic tables to accompany Modern engineering thermodynamics - Balmer, Robert T. (Boston : Academic Press, 2011)
This booklet is provided at no extra charge with new copies of Balmer's Modern Engineering Thermodynamics. It contains two appendices. Appendix C contains 40 thermodynamic tables, and Appendix D consists of 6 thermodynamic charts. These charts and tables are provided in a separate booklet to give instructors the flexibility of allowing students to bring the tables into exams. The booklet may be purchased separately if needed.